Implementation of AIK and Arabic Language in Supporting the Realization of Wasathiyyah Islam at PTMA in Indonesia - Mahyudin Ritonga; Apri Wardana Ritonga; Ayu Desrani (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
The implementation of wasathiyyah Islam has a vital role in realizing the understanding and mindset of moderate students. This study aims to describe the implementation of AIK and Arabic in Muhammadiyah and Aisyiyah Colleges (PTMA) in realizing wasathiyyah Islam in Indonesia. This study uses a qualitative approach with the method of literature. Sources of data in the form of scientific articles, scientific reports, books, and relevant documents. Research data were collected, selected, interpreted, and analyzed using descriptive content analysis. The results of this study indicate that the implementation of AIK and Arabic in PTMA has a major influence in realizing wasathiyyah Islam in Indonesia through the material contained in AIK I, AIK II, AIK III, and AIK IV which examines the strengthening of the values of faith, morality, mu'amalah, humanity, Muhammadiyah, as well as the fulfillment of social, spiritual, and intellectual aspects that are adapted according to the progress of the times. The implementation of AIK and the Arabic language forms each PTMA graduate with the following characteristics: having a moderate mindset and personality, not taking extreme, radical, and liberal actions, having a character identity, generous, having a leadership spirit, and caring about the problems of the people and the nation. The researcher recommends further research to examine the effectiveness of the implementation of AIK and Arabic in supporting the realization of wasathiyyah Islam in PTMA with larger variables and research objects.